2020
DOI: 10.1080/02656736.2020.1836406
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced antitumor efficacy through microwave ablation combined with a dendritic cell-derived exosome vaccine in hepatocellular carcinoma

Abstract: Aim: To investigate the antitumor efficacy of microwave ablation combined with dendritic cell-derived exosomes (Dex) or dendritic cells (DC) in treating hepatocellular carcinoma using a tumor-bearing mouse model. Methods: We used a bilateral tumor-bearing mouse model treated with MWA, MWA þ DC (DC-combined group) or MWA þ Dex (Dex-combined group). Following tumor ablation on one side, the tumor volume on the contralateral side was monitored. The proportions of CD8 þ (cytotoxic) T cells and regulatory T (Treg) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Similarly, when rechallenged in the contralateral flank with the same cell line, the combination therapy group showed an earlier tendency to suppress tumor growth compared with MWA alone. The second study [ 71 ] was designed similarly but included a dendritic cell-derived exosome group. They found no significant differences between MWA plus dendritic cells or MWA plus dendritic cell-derived exosomes: both groups resulted in higher levels of CD8+ T cells and IFN-γ and lower levels of Treg cells and IL-10 compared with MWA alone.…”
Section: Evidence For the Immunogenicity Of Ablationmentioning
confidence: 99%
“…Similarly, when rechallenged in the contralateral flank with the same cell line, the combination therapy group showed an earlier tendency to suppress tumor growth compared with MWA alone. The second study [ 71 ] was designed similarly but included a dendritic cell-derived exosome group. They found no significant differences between MWA plus dendritic cells or MWA plus dendritic cell-derived exosomes: both groups resulted in higher levels of CD8+ T cells and IFN-γ and lower levels of Treg cells and IL-10 compared with MWA alone.…”
Section: Evidence For the Immunogenicity Of Ablationmentioning
confidence: 99%
“…Table 5 [ 70 , 71 ] shows the self-derived exosomes from dendritic cells as potential therapeutic factors. Data showed exosomes isolated from dendritic cells could inhibit tumor growth and improve the immune response.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, this group showed that purified DEXs successfully carried melanoma epitopes and induced potent anti-tumor immune responses, thereby slowing tumor progression. Recently, a DEX-based vaccine combined with microwave ablation was reported to inhibit tumor growth in hepatocellular carcinoma (HCC) mouse models compared to microwave ablation (a common therapy for HCC patients) alone, in this case, the tumor disappeared 10 days after microwave ablation in combination with DEX injection (92). Additionally, HCC features a high expression level of a-fetoprotein (AFP), which has been used as an HCC antigen for monitoring and diagnosis (93).…”
Section: Exosome-based Vaccines As a Cancer Therapeutic Strategymentioning
confidence: 99%